Relasi Nikah Siri dan Poligami pada Masyarakat di Kecamatan Bendahara Kabupaten Aceh Tamiang Perspektif UU Nomor 1 Tahun 1974 - Maulana Ira (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The unregistered nature of marriages in Indonesia is a persistent issue due to the failure to register marriages with the state through the Office of Religious Affairs (KUA). The trend is toward unregistered marriages, which often lead to polygamy. This paper aims to uncover the relationship between unregistered marriages and their various factors within the community of Bendahara District, Aceh Tamiang Regency. Empirical juridical methods are used to examine the actual laws within the community. The results demonstrate a strong correlation between unregistered marriages and the desire for polygamy. The causes are diverse, ranging from psychological and biological factors to economic and social factors, to the difficulty of state regulations regarding polygamy.